Risk Factors for EGFR (Epidermal Growth Factor Receptor) Gene Mutations in Lung Adenocarcinoma Patients at Arifin Achmad Hospital, Riau Province - Riensya, Bayu Aulia; Munir, Sri Melati; Wijaya, Dewi (Jurnal Respirologi Indonesia, 2024)
Background: Lung cancer is the first cause of oncological death worldwide. Guidelines made by various cancer associations, including PDPI-IASTO, regarding NSCLC recommend that all advanced stages of NSCLC undergo target genetic testing, such as EGFR mutations. The incidence of EGFR mutations in Asian populations is quite high.Methods: This was a retrospective observational analytic study with a cross-sectional study design.Results: The most unmodifiable risk factors were age ≥45 years (81.4%), male sex (70.6%), location of lung cancer on the right (52.9%), cancer size of ≥5 cm (100%), M1a metastases (57.8%), and no family history of malignancy (97.1%). The smoking status (ex-smoker) (P=0.022; OR=4.3; 95% CI=1.24-15.57), sex (male) (P=0.007; OR=3.409; 95% CI=1.406-8.268), and metastatic status (M1a) (P=0.025; OR=0.203; 95% CI=0.05-0.821) were the dominant risk factors that affected the incidence of EGFR mutations in patients with lung adenocarcinoma at Arifin Achmad Hospital.Conclusion: Male, ex-smokers, and metastatic status (M1a) were the dominant risk factors for the incidence of EGFR mutations in lung adenocarcinoma patients at Arifin Achmad Hospital.